The Use of Instagram to Develop Students’ Writing Skill at SMK Darussalam Makassar - Sitti Aisyah; Isnaeni Wahab; Nuraeni Nuraeni; Novalia Tanasy (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2023)
One type of writing exercise that concentrate on describing people, places, things, emotions, and feelings is descriptive text. While Instagram is a platform for sharing emotions and experiences from daily life, recounting such events in class encourages students to utilize their imaginations to reflect on their own lives and events that have already happened. Therefore, Instagram can offer several helpful components to help students improve their writing skills. In this study, the data were analyzed by the researcher using a quantitative approach with pre-experimental research. It was the method that used one group pretest and post-test design. In one group pre-test and post- test design, used a single group to measure or observe. The population of this research was class X TKJ 1 at SMK Darussalam Makassar, and there were 28 students in the samples. Assessments (pre- and post-tests) were the instrument employed in this study. The statistical findings show that the students' average post-test score was higher than their average pre-test score (70.11), at 86.61. This analysis of the t-test indicates that the t-test's value (16.511) is higher than its value (1.703) with 24 as the degree of freedom. This indicates a significant difference. In light of the fact that Ho is disproved and H1 is widely accepted, it is possible to conclude that using Instagram as a teaching and learning tool can help students improve their capacity to create descriptive writing. Instagram is a great tool for English teachers to use as a teaching tool since it offers a variety of implementation materials to break up the monotony of teaching writing to students.